2022
DOI: 10.1186/s13287-022-02980-3
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose-derived mesenchymal stem cells-derived exosomes encapsulated in pluronic F127 hydrogel promote wound healing and regeneration

Abstract: Background Large area skin trauma has always been a great challenge for both patients and clinicians. Exosomes originating from human adipose-derived mesenchymal stem cells (hADSCs) have been a novel promising cell-free treatment in cutaneous damage repair. Nevertheless, the low retention rate of exosomes post-transplantation in vivo remains a significant challenge in clinical applications. Herein, we purposed to explore the potential clinical application roles of hADSCs-Exos encapsulated in fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 71 publications
0
54
0
2
Order By: Relevance
“…The release of EVs from hydrogels is often characterized using a micro bicinchoninic acid (BCA) assay, ELISA, or fluorescent labeling. The BCA assay can be used to determine the percentage of released EVs by mixing the EVs with the hydrogel, placing the mixture in the upper chamber of a 24-well transwell plate, and measuring the protein concentration in the lower chamber at different time points [ 167 ]. Similarly, a dynamic dialysis method can be used to detect the release of EVs by placing the EV-loaded hydrogel in a dialysis bag and placing the bag in a constant-temperature phosphate buffered saline (PBS) solution.…”
Section: Ev-loaded Hydrogel Preparations and Application Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The release of EVs from hydrogels is often characterized using a micro bicinchoninic acid (BCA) assay, ELISA, or fluorescent labeling. The BCA assay can be used to determine the percentage of released EVs by mixing the EVs with the hydrogel, placing the mixture in the upper chamber of a 24-well transwell plate, and measuring the protein concentration in the lower chamber at different time points [ 167 ]. Similarly, a dynamic dialysis method can be used to detect the release of EVs by placing the EV-loaded hydrogel in a dialysis bag and placing the bag in a constant-temperature phosphate buffered saline (PBS) solution.…”
Section: Ev-loaded Hydrogel Preparations and Application Methodsmentioning
confidence: 99%
“…By placing a hydrogel loaded with PKH26-labeled EVs in a 24-well plate filled with PBS, the EV release rate can be calculated by measuring PKH26 fluorescence in the supernatant over time [ 72 ]. In in vivo experiments, hydrogels loaded with PKH26-labeled EVs were applied to traumatic wound surfaces and the release rate was calculated by measuring the fluorescence intensity of PKH26 in tissues at different time periods [ 72 , 167 ]. Likewise, experiments in which EVs were labeled with DiI showed that DiI-labeled EVs were gradually released from hydrogels with increasing incubation time ( Fig.…”
Section: Ev-loaded Hydrogel Preparations and Application Methodsmentioning
confidence: 99%
See 3 more Smart Citations